THE RELATIONSHIP BETWEEN DIET AND BREAST CANCER RISK: A REVIEW OF THE LITERATURE - Wahyuni, Briliansa Septi Dwi; Faizah, Zakiyatul (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Breast cancer is a common cancer that causes a high mortality rate in women. There are risk factors for breast cancer that cannot be changed and those that can be changed. Diet plays an important role as a modifiable risk factor in preventing breast cancer. An unhealthy diet is one of the factors that trigger breast cancer. Conversely, a healthy diet can help reduce the risk of breast cancer. To determine the relationship between diet and breast cancer risk. Literature review with reference to articles through the online database, Pubmed, with the keywords diet AND dietary AND food AND nutrition AND breast cancer AND risk factor published in 2013-2023. Identified 11 articles showed an association between diet and breast cancer risk. Articles found that diets rich in fruits, vegetables, soy, cheese were associated with a reduced risk of breast cancer, whereas high consumption of dairy, sugar, fat, alcohol was associated with an increased risk of breast cancer. It was also found that diets rich in poultry, fish, eggs, fruit juice, milk (450 g/day), yogurt, whole grains, nuts, had no association with cancer risk. Diet has an effect on breast cancer.